Short communication: Algal leaf spot associated with Cephaleuros virescens 1 Ulvophyceae) - ANURAG SUNPAPAO; MUTIARA K. PITALOKA; SIWARET ARIKIT (Society for Indonesian Biodiversity, 2016)
Sunpapao A, Pitaloka MK, Arikit S. 2015. Algal leaf spot associated with Cephaleuros virescens (Trentepohliales, Ulvophyceae) on Nephelium lappaceum in Thailand. Biodiversitas 17: 31-35. Algal leaf spot disease of Nephelium lappaceum (rambutan) was observed in southern Thailand. The algae were isolated on Bold’s basal medium (BBM) a nd identified based on appearance of the lesions, algal morphology and molecular properties. Characteristics of the filamentous thallus cells, sporangiophores, sporangia, gametes and zoospores were clarified. A portion of the 18S small subunit rRNA was amplified to validate the morphological identification by sequence similarity. To summarize the main results, the plant parasite causing algal leaf spot was identified as Cephaleuros virescens, and in sequencing-based phylogenetic analysis the Cephaleuros PSU-R5.1 isolate from rambutan grouped with the algae in genus Cephaleuros. This confirms C. virescens as a causal organism of algal leaf spot disease on rambutan in southern Thailand.